An Annotated Checklist of the Non-native Plants Species of Campus of Universitas Indo Global Mandiri, Palembang, Sumatra - Aprillia, Ina; Nur Arifah; Gusti Ayu Widayanti; Diah Komala Sari (BIO PALEMBANICA, 2024)
The research on the inventory of invasive alien species in the area of Universitas Indo Global Mandiri (UIGM) aims to identify the alien and invasive species present on campus, so that the potential impacts of their presence can be assessed. The method used in this activity is the exploration method, where the researcher will explore the area around the campus to collect data on plants. The results obtained from this research indicate that there are 77 plant species consisting of 40 families. The families with the highest number of species are Apocynaceae and Araceae (7 species). Among the species identified, there are 42 alien species, 26 native species, and 9 invasive species.